History, time, meaning, and memory ideas for the sociology of religion - Denison, Barbara J. (Religion and the Social Order, 2011)
It can be said that history is poor sociology that does not account sufficiently for present social circumstances, while sociology is bad history in that it does not go back in time. This volume in the Religion and Social Order series sets out to address these conjoint problems of history and sociology within the disciplinary boundaries of the sociology of religion. History has such a fickle nature that it has seen religion hold varied and different places within the timeline of sociological thought. Religion had a high level of importance among the early founders of sociology. A perceived decline of significance for religion by sociology in the latter half of the twentieth century mirrored the changing social location of religion. The increase in world fundamentalisms, religious movements, private spiritualities and other indicators in the millennial age have brought a renaissance to this longstanding subdiscipline and shown that religion is far from extinction.